Infant baptism and the disposition to saving faith. Issue 4 (November 2022) - Crisp, Oliver D.
Abstract: Reformed accounts of infant baptism are usually covenantal and promissory in nature. They are about bringing the child into the ambit of the visible church in the hope the infant will own the faith upon reaching the age of reason. This paper sets out an alternative Reformed account of baptism, drawing on the Scottish confessional tradition. On this account, infants have a disposition to faith conveyed to them in baptism that will in due course become dispositional faith exercised in saving faith. Thus, baptism involves regeneration – or something close to it.